Hubungan Status Gizi, Kualitas Tidur dan Aktivitas Fisik dengan Siklus Menstruasi pada Remaja Putri di SMAN 98 Jakarta: Relationship of Nutritional Status, Sleep Quality and Physical Activity with The Menstrual Cycle in Adolescent Girls at SMAN 98 Jakarta - Anggi Ayuni Moulinda; Iin Fatmawati Imrar; Ikha Deviyanti Puspita; M. Ikhsan Amar (UNIVERSITAS NGUDI WALUYO, 2023)
Menstrual disorders are common in adolescents girl. Disorders that occur include delayed menstruation, irregular menstrual cycles, pain in body areas, and abnormal bleeding during menstruation. According to WHO, 75% of adolescent girls experience menstrual cycle disorders. The purpose of this study was to analyze the relationship between nutritional status, sleep quality and physical activity with the menstrual cycle in adolescent girls at SMAN 98 Jakarta. This research is a quantitative study using a cross-sectional study design with the sampling technique used is stratified random sampling and obtained a sample of 100 respondents. The results of the univariate analysis showed the prevalence of menstrual cycle disorders in adolescent girls at SMAN 98 Jakarta was 41%. The results of the chi-square test showed that there was a significant relationship between nutritional status (p-value = 0.018) and physical activity (p-value 0.003) with the menstrual cycle, while there was no significant relationship between sleep quality (p-value = 0.136) and the menstrual cycle. menstruation. The conclusion obtained in this study is that there is a significant relationship between nutritional status and physical activity in the menstrual cycle and there is no significant relationship between sleep quality and the menstrual cycle. ABSTRAKGangguan menstruasi merupakan hal sering terjadi pada remaja putri. Gangguan yang terjadi diantaranya tertundanya menstruasi, siklus menstruasi tidak teratur, nyeri pada area tubuh, dan perdarahan di luar kewajaran saat menstruasi. Menurut WHO sebesar 75% remaja putri mengalami gangguan siklus menstruasi. Tujuan penelitian ini ialah menganalisis hubungan status gizi, kualitas tidur dan aktivitas fisik dengan siklus menstruasi pada remaja putri di SMAN 98 Jakarta. Penelitian ini adalah penelitian kuantitatif dengan menggunakan desain study cross-sectional dengan teknik sampling yang digunakan yaitu stratified random sampling dan didapatkan sampel sebanyak 100 responden. Hasil analisis univariat menunjukkan prevalensi gangguan siklus menstruasi pada remaja putri di SMAN 98 Jakarta sebesar 41%. Hasil uji chi-square menunjukkan terdapat hubungan yang signifikan antara status gizi (p-value = 0,018) dan aktivitas fisik (p-value 0,003) dengan siklus menstruasi, sementara itu tidak ada hubungan signifikan antara kualitas tidur (p-value = 0,136) dengan siklus menstruasi pada remaja putri di SMAN 98 Jakarta. Kesimpulan yang diperoleh dalam penelitian ini terdapat hubungan signifikan antara status gizi dan aktivitas fisik pada siklus menstruasi serta tidak ada hubungan signifikan antara kualitas tidur dengan siklus menstruasi.